AKIBAT HUKUM DARI AKTA JUAL BELI TANAH YANG DIBACAKAN PPAT YANG BERADA DILUAR WILAYAH KERJANYA BERDASARKAN PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 (STUDI KASUS PPAT X di DEPOK) - , UMELVA, Dr.Sutanto.SH.MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research into Legal Consequences of Sales and Purchase Deed Which Was Read by Official Certifier of Title Deeds (hereinafter to be referred as PPAT) Who Was Beyond His Jurisdiction According to Government Regulation Number 37 of 1998 (Case Studies of PPAT X in Depok) aims to determine legal consequences for the PPAT who was read Sales and Purchase Deed beyond his jurisdiction according to Governmental Regulation Number 37 of 1998 (Case Studies of PPAT X in Depok) and legal consequences against the deed who was read by PPAT beyond his jurisdiction. The study applying normative juridical approach, i.e. study for the law within the existing legislations / regulations concerning legal consequences for PPAT who was read Sales and Purchase Deed beyond his jurisdiction, which are specifically set forth in the Governmental Regulation Number 37 of 1998. Analysis on the study is a qualitative analysis, i.e. fundamental analysis on the quality and factual characteristic prevails on the community. Result of the study to the legal consequences for PPAT who was read Sales and Purchase Deed beyond his jurisdiction might dishonorably discharged from his position due to serious violations, and the legal consequences to the Deed which was read by the PPAT who was beyond his jurisdiction so the probative force of such deed may being relegated into a private deed and for the third party who has vested interest to such deed may harness the situation.